2013
DOI: 10.1002/hed.23335
|View full text |Cite
|
Sign up to set email alerts
|

Complex adult laryngotracheal reconstruction with a prefabricated flap: A case series

Abstract: A delayed prefabricated graft using auricular cartilage in a radial forearm free flap is a viable surgical intervention in patients with complex adult LTS who are not candidates for conventional approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…Urken et al reported one of the first descriptions of reconstructing a hemicricoid and hemilaryngeal defect, with a sensate radial forearm free flap using costal cartilage in patients with partial laryngopharyngectomies . Prefabricated radial forearm free flaps using auricular cartilage has also been described in both the adult and pediatric populations for laryngotracheal stenosis . These cases demonstrate the utility in composite free flaps in airway reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urken et al reported one of the first descriptions of reconstructing a hemicricoid and hemilaryngeal defect, with a sensate radial forearm free flap using costal cartilage in patients with partial laryngopharyngectomies . Prefabricated radial forearm free flaps using auricular cartilage has also been described in both the adult and pediatric populations for laryngotracheal stenosis . These cases demonstrate the utility in composite free flaps in airway reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Restoring the integrity of the complete ring of the cricoid cartilage and mucosa can ameliorate some of these issues by recreating structural stability and internal lining, but this remains challenging . Recently, vascularized carriers have been implemented for transplanting cartilage and bone to reconstruct cricoid defects …”
Section: Introductionmentioning
confidence: 99%
“…The cartilage graft is then placed with its convex aspect against the subcutaneous fat within the suprafascial plane of the SCAIF and tacked in place with absorbable monofilament suture. The elevated portions of the SCAIF are then replaced, and the incision is closed in standard fashion.…”
Section: Methodsmentioning
confidence: 99%
“…In 2013, Detwiller and colleagues described a technique to repair complicated TS utilizing auricular cartilage graft prefabricated within the radial forearm free flap (pRFFF) in patients deemed unsuitable for primary tracheal resection . Although pRFFF reconstruction has been successful in these high‐risk patients, the procedure adds increased operative time, requires microvascular surgery experience and training, and presents a risk of donor site complications such as tendon exposure especially among diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Airway reconstruction with microvascular free flaps using both autologous and prosthetic composite grafts has been previously described in the adult population. Detwiller et al demonstrated that a delayed prefabricated graft using auricular cartilage and a radial forearm free flap was a viable reconstructive option in an adult series with complex laryngotracheal stenosis. This method allowed for transfer of a vascularized cartilage graft in patients who had unsuccessful previous airway reconstructions.…”
Section: Introductionmentioning
confidence: 99%